2020
DOI: 10.3758/s13428-020-01379-3
|View full text |Cite
|
Sign up to set email alerts
|

A mobile approach-avoidance task

Abstract: When the original approach-avoidance task (AAT; Solarz, 1960) that measures these tendencies was redesigned to run on regular desktop computers, it made the task much more flexible but also sacrificed some important behavioral properties of the original task-most notably its reliance on physical distance change (Chen & Bargh, 1999). Here, we present a new, mobile version of the AAT that runs entirely on smartphones and combines the flexibility of modern tasks with the behavioral properties of the original AAT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 58 publications
(98 reference statements)
2
46
0
Order By: Relevance
“…The authors found what they termed a "directtouch effect" such that participants who performed the task on a touchscreen made more hedonic food choices than those who performed the task with a non-touch interface. Finally, Zech and colleagues implemented an approach-avoidance task (AAT) on a smartphone that could be moved closer or further away to simulate naturalistic grasping or rejection movements (Cring, 2017;Zech, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found what they termed a "directtouch effect" such that participants who performed the task on a touchscreen made more hedonic food choices than those who performed the task with a non-touch interface. Finally, Zech and colleagues implemented an approach-avoidance task (AAT) on a smartphone that could be moved closer or further away to simulate naturalistic grasping or rejection movements (Cring, 2017;Zech, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If one pulls a joystick to oneself, it is ambiguous whether that motion reflects the self (i.e., ‘moving myself away from the stimulus’, indicating avoidance) or whether the motion reflects the stimulus (i.e., ‘moving the stimulus to me’, indicating approach). Thus, for a more natural experience, reminiscent of the original test, yet easy to run and quantify, Zech et al [ 22 ] developed a mobile version of the AAT (mAAT), in which images are presented on a smartphone screen that participants have to push away or pull toward themselves. Indeed, it was found that participants were faster when they had to approach positive stimuli (happy faces) or avoid negative stimuli (angry faces), compared to when these instructions were reversed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for a more natural experience, reminiscent of the original test, yet easy to run and quantify, Zech et al [ 22 ] developed a mobile version of the AAT (mAAT), in which images are presented on a smartphone screen that participants have to push away or pull toward themselves. Indeed, it was found that participants were faster when they had to approach positive stimuli (happy faces) or avoid negative stimuli (angry faces), compared to when these instructions were reversed [ 22 ]. The mAAT seems a particularly suitable tool to measure approach–avoidance in the domain of food, given that food has a very natural, unambiguous relation to approach and avoidance (bringing food to the mouth, or pushing it away).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations